2020
DOI: 10.3389/fphar.2020.561334
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV Natural Products With the Potential to Inhibit SARS-CoV-2 (COVID-19)

Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), known to cause the disease COVID-19, was declared a pandemic in early 2020. The objective of this review was to collate information regarding the potential of plants and natural products to inhibit coronavirus and targets associated with infection in humans and to highlight known drugs, which may have potential activity against SARS-CoV-2. Due to the similarity in the RNA genome, main proteases, and primary host receptor between SARS-CoV and SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 110 publications
(186 reference statements)
0
110
0
1
Order By: Relevance
“…Since SARS-CoV-2 has become a pandemic infection with relevant health issues, the scientific community carried out much effort for the identification of potential drug targets to tackle this virus infection. Recently, several articles have been published, most of them based on the virtual screening of natural occurring compounds towards viral target proteins [ 152 , 153 , 154 , 155 ].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Since SARS-CoV-2 has become a pandemic infection with relevant health issues, the scientific community carried out much effort for the identification of potential drug targets to tackle this virus infection. Recently, several articles have been published, most of them based on the virtual screening of natural occurring compounds towards viral target proteins [ 152 , 153 , 154 , 155 ].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…(-)-Epigallocatechin gallate, rutin and cyanidin-3-O-glucoside are flavonoids, a biologically active class of the phenolic compounds (Bonvino et al, 2018 ). In a recent literature review conducted by Verma et al, the flavonoids were found to be the largest class of compounds with potential activity against coronaviruses (Verma et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that NPs/SMs are a rich source of drug potential leads against coronaviruses due to their pronounced structural diversity and complexity. Several compilations of pre-2020 findings on NPs/SMs with activity against coronaviruses were recently reported, some of which could serve as leads for the development of new drugs [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Among the identified molecules the majority is represented by NPs ( Figure 2 a) and most of them have been found as inhibitors of SARS-CoV ( Figure 2 b).…”
Section: Nps With Anti-hcov Potentialmentioning
confidence: 99%